A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Patterns and thresholds for soil pH across Europe in relation to soil health and degradation - Inma Lebron; Christopher J. Feeney; Sabine Reinsch; Nima Shokri; Mehdi H. Afshar; Steve Lofts; Rob Griffiths; David Fidler; Briony Jones; Panos Panagos; Kasia Sawicka; Aidan M. Keith; et al. (CATENA, 2025)

What controlled the occurrence of more than 116,000 human-mapped landslides triggered by Cyclone Gabrielle, New Zealand? - Chris Massey; Kerry Leith; Tom R Robinson; Biljana Lukovic; Sam McColl; Trevor Carey-Smith; Brenda Rosser; Liam Wotherspoon; Hugh Smith; Harley Betts; Rob Buxton; Janine Bidmead (Landslides, 2025)
This paper uses an extract of 116,655 landslide source areas from the >160,000 human-mapped landslides contained in the Version One (V1.0) landslide inventory triggered by Cyclone Gabrielle (11–17 February 2023). It describes the analysis of the human-mapped landslide distribution and the relationships between landslide occurrence, their susceptibility factors, and their hydrological forcing factors. The results show that rain is one of the main controlling factors on landslide probability, but the relationship is complex. Our results show the amount of 24-h rain becomes less important, relative to other landslide susceptibility factors, at high (>220 mm) to very high (>330 mm) 24-h rainfalls, suggesting that such extreme rain amounts may not drive the highest probability of landslide occurrence. Results also suggest that the 24-h rainfalls experienced by some areas during Cyclone Gabrielle were likely to have been sufficiently high enough to “overprint” antecedent soil water conditions. In these overprint areas, soil-water conditions prior to Cyclone Gabrielle rainfall may not have materially influenced the spatial landslide distributions. The results from this study suggest that during a storm, more intense rainfall may not directly translate to increasing probability of landslide occurrence; however, it may diminish the effect of pre-event soil water content.

Adult survival has a stronger role than productivity in the annual population change of European songbirds - Inari Nousiainen; Laura Bosco; Petteri Lehikoinen; Rob Robinson; Juan Arizaga; Jaroslav Cepák; Wolfgang Fiedler; Olaf Geiter; Ian Henshaw; Christof Herrmann; Marc Illa; Henk P. van der Jeugd; et al. (Oecologia, 2025)
Biodiversity is decreasing at an alarming rate, and there is an urgent need to understand the demographic drivers behind population declines. Therefore, it is important to study the different stages of a species’ life cycle, including adult survival and productivity. It is still poorly understood whether adult survival or productivity has a stronger role in population change, and how the role of adult survival and productivity varies spatially in relation to species’ traits. We used bird ringing data from the European Constant Effort Sites (EuroCES) project from the years 2000 to 2021, with 1.2 million captures of 33 songbird species from ten European countries. We investigated the role of productivity and adult survival in annual population change and how it was affected by spatio-climatic gradient (measured as average breeding season temperature per country), migratory strategy (long- vs. short-distance and sedentary birds), and breeding habitat (forest vs. reeds) using linear mixed effect models. Overall, our results show that adult survival is a more important driver of annual population change than productivity within European songbirds. The importance of adult survival and productivity varied spatially, both having a weaker influence in warmer regions. Furthermore, the role of adult survival was stronger for long-distance migrants compared to short-distance migrants. Acknowledging that adult survival has a stronger role in annual population change than productivity can help design more robust conservation actions, especially regarding long-distance migratory songbirds.

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Associations of per- and polyfluoroalkyl substances, polychlorinated biphenyls, organochlorine pesticides, and polybrominated diphenyl ethers with oxidative stress markers: A systematic review and meta-analysis - Jiawen Carmen Chen; Brittney O. Baumert; Yijie Li; Yiping Li; Shudi Pan; Shante Robinson; Bruna Rubbo; Elizabeth Costello; Jie He; Hailey Hampson; Emily Beglarian; Sarah Rock; et al. (Environmental Research, 2023)

Using Multiple Geophysical Methods to Refine a Stratigraphic Conceptual Site Model at a Nuclear Waste Site - Judith Robinson; James St. Clair; Jonathan Thomle; Piyoosh Jaysaval; Joaquin Cambeiro; Kelsey Peta; Frederick Day-Lewis; Rob D. Mackley (Environmental Processes, 2023)

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

The mental health of asbestos-exposed subjects with pleural abnormalities - Peter Franklin; Monique Robinson; Patrick Abaogye-Sarfo; Latha Samuel; Nola Olsen; Rob Mina; A. W. Musk; Alison Reid (International Archives of Occupational and Environmental Health, 2015)

Identifying qualitative effects of different grazing types on below‐ground communities and function in a long‐term field experiment - Catriona A. Macdonald; Michael J. Crawley; Denis J. Wright; Justin Kuczynski; Lucinda Robinson; Rob Knight; Waleed Abu Al‐Soud; Søren J. Sørensen; Ye Deng; Jizhong Zhou; Brajesh K. Singh (Environmental Microbiology, 2015)
Summary Herbivory is an important modulator of plant biodiversity and productivity in grasslands, but our understanding of herbivore‐induced changes on below‐ground processes and communities is limited. Using a long‐term (17 years) experimental site, we evaluated impacts of rabbit and invertebrate grazers on some soil functions involved in carbon cycling, microbial diversity, structure and functional composition. Both rabbit and invertebrate grazing impacted soil functions and microbial community structure. All functional community measures (functions, biogeochemical cycling genes, network association between different taxa) were more strongly affected by invertebrate grazers than rabbits. Furthermore, our results suggest that exclusion of invertebrate grazers decreases both microbial biomass and abundance of genes associated with key biogeochemical cycles, and could thus have long‐term consequences for ecosystem functions. The mechanism behind these impacts are likely to be driven by both direct effects of grazing altering the pattern of nutrient inputs and by indirect effects through changes in plant species composition. However, we could not entirely discount that the pesticide used to exclude invertebrates may have affected some microbial community measures. Nevertheless, our work illustrates that human activity that affects grazing intensity may affect ecosystem functioning and sustainability, as regulated by multi‐trophic interactions between above‐ and below‐ground communities.

A microbiological survey of Montserrat Island hydrothermal biotopes - Tony Atkinson; Steven Cairns; D. A. Cowan; Michael J. Danson; David W. Hough; D. Barrie Johnson; Paul R. Norris; Neil Raven; Clare Robinson; Rob Robson; Richard J. Sharp (Extremophiles, 2000)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)